Tracing Malay learners' variations in learning strategies / Mohamad Fadhili Yahaya - Yahaya, Mohamad Fadhili (Universiti Teknologi MARA, Perlis, 2003)
Rural Malay language learners have generally been depicted as being low in their performance. This may be due to the weak strategies in language learning. Having been labelled as such, the study embarked on substantiating the claim. It tried to examine the learning strategies of the learners as well as to establish relationships between language learning strategies and language performance. The study found that learners were limited in their use of the learning strategies. In terms of the relationships of the variables to learners' language performance, the findings also displayed there were some significant correlations to learners' learning strategies.